2022
DOI: 10.1002/lno.12211
|View full text |Cite
|
Sign up to set email alerts
|

Sponge contribution to the silicon cycle of a diatom‐rich shallow bay

Abstract: In coastal systems, planktonic and benthic silicifiers compete for the pool of dissolved silicon, a nutrient required to make their skeletons. The contribution of planktonic diatoms to the silicon cycle in coastal systems is often well characterized, while that of benthic silicifiers such as sponges has rarely been quantified. Herein, silicon fluxes and stocks are quantified for the sponge fauna in the benthic communities of the Bay of Brest (France). A total of 45 siliceous sponge species living in the Bay ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…This habitat occupies a small area of the Bay (1.44 km 2 of the total 133.13 km 2 , i.e., 1.1%). In this ecosystem, assemblages of maerl (coralline red algae) serve as substrate for a highly diverse benthic community, including more than 20 species of sponges 13 . Among them, H. perlevis (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This habitat occupies a small area of the Bay (1.44 km 2 of the total 133.13 km 2 , i.e., 1.1%). In this ecosystem, assemblages of maerl (coralline red algae) serve as substrate for a highly diverse benthic community, including more than 20 species of sponges 13 . Among them, H. perlevis (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, H. perlevis (Fig. 1 a) is the dominant species in terms of both abundance (53%) and biomass (64%) 13 . It has a moderate content of siliceous skeleton derived from the production of a single, mid-size (175–475 µm long) type of needle-like silica spicule, which is homogenously distributed throughout the sponge body 31 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More questionable proposals suggest some Precambrian fossil vestiges to be sponge silica skeletons (Muscente et al, 2015). The sponge skeletons accumulated in marine sediments make important local to regional silica reservoirs (Rützler and Macintyre, 1978;Bavestrello et al, 1996;Chu et al, 2011;Gutt et al, 2013;Murillo et al, 2016;Maldonado et al, 2021;Loṕez-Acosta et al, 2022). A first quantification of the deposition and burial of sponge skeletons, which occurs more markedly on continental margins and around seamounts, revealed that these processes lead to a substantial Si sink in the global ocean (Maldonado et al, 2019).…”
Section: Introductionmentioning
confidence: 99%